Fragmented Integration: The Nova Scotia Steel and Coal Company and the Anatomy of an Urban-Industrial Landscape, c. 1912 - McCann, L. D. (Urban History Review / Revue d'histoire urbaine, 1994)
This paper examines how forces of fragmentation within the Maritimes contribute a partial but important explanation of the urban-industrial collapse that marked the region in the early 20th century. Specifically, weaknesses that affected the spatial strategies of the vertically-integrated industrial giant, the Nova Scotia Steel and Coal Company, provide evidence of limited interaction within the Maritime urban system. Profits from exporting staples, pig iron, and steel products to foreign and national markets, although initially aided by tidewater location and control over all phases of production, were not sufficient to overcome, in the long-run, such forces of fragmentation as dispersed and limited regional markets, increased costs of producing poor quality resources, or the minimal presence of external economies. With "Scotia's" eventual demise, towns like Sydney Mines, Trenton, and New Glasgow suffered economic and population decline.